High-power mid-infrared ZGP optical parametric oscillator directly pumped by pulsed Tm:YLF laser at 1908 nm. (June 2023) - Wei, Xingbin; Zhang, Song; Liu, Zhengyi; Ye, Xianlin; Yin, Wenlong; Ren, Huaijin; Kang, Bin; Yuan, Zerui; Wang, Weimin; Ma, Yi
Highlights: First demonstration of a ZGP optical parametric oscillator (OPO) directly pumped by a pulsed Tm:YLF laser at 1.908 μm. Improved ZGP crystal with state-of-art low absorption coefficient and high laser-induced damage threshold at 1.908 μm. Highest output power and efficiency for any kind of Tm laser directly-pumped OPOs. Superior overall photon efficiency of 92.4 % from the 793 nm LD to mid-infrared (MIR) lasers. New reference for high-power, high-efficiency MIR OPOs for practical and compact applications. Abstract: This paper presents the first demonstration of a mid-infrared optical parametric oscillator (MIR OPO) based on ZGP crystal which was directly pumped by an acousto-optical Q-switched Tm:YLF laser at 1.908 μm. Profited from the improved quality of ZGP crystal with low absorption coefficient (<0.04 cm −1 ) and high laser-induced damage threshold (>3 J/cm 2 ) at 1.908 μm, output power of 17.8 W for both the 3.53 μm signal and 4.15 μm idler lasers was achieved when the double-pump-pass, doubly-resonated ZGP OPO was pumped at 28.6 W. To the best of our knowledge, this is the highest output power and efficiency for any kind of Tm-laser directly-pumped OPOs.